2018
DOI: 10.3389/fmicb.2018.01600
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Microbiota Alterations Associated With Diarrhea-Predominant Irritable Bowel Syndrome

Abstract: Altered gut microbiota are assumed to be involved in the pathogenesis of irritable bowel syndrome (IBS). However, gut microbiota alterations reported in different studies are divergent and sometimes even contradictory. To better elucidate the relationship between altered gut microbiota and IBS, we characterized fecal microbiota of diarrhea-predominant IBS (IBS-D) patients and further explored the effect of rifaximin on gut microbiota using bacterial 16S rRNA gene-targeted pyrosequencing. In our study, IBS-D pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
91
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 105 publications
(109 citation statements)
references
References 31 publications
9
91
0
1
Order By: Relevance
“…The microbial richness and diversity increased in duodenal mucosa while decreased in rectal mucosa in SIBO + IBS‐D. In condition of SIBO, bacteria thriving and ectopic colonization resulted in raised microbial diversity in the small intestine, as well as in the duodenum; on the contrary, overgrowth of the dominant strains in the colorectum was speculated to restrain the biological diversity . There were marked changes of both duodenal and rectal mucosal microbiota in SIBO + compared with SIBO − IBS‐D patients, with increased MDI values but completely distinct genera increase or decrease between the duodenum and the rectum.…”
Section: Discussionmentioning
confidence: 98%
“…The microbial richness and diversity increased in duodenal mucosa while decreased in rectal mucosa in SIBO + IBS‐D. In condition of SIBO, bacteria thriving and ectopic colonization resulted in raised microbial diversity in the small intestine, as well as in the duodenum; on the contrary, overgrowth of the dominant strains in the colorectum was speculated to restrain the biological diversity . There were marked changes of both duodenal and rectal mucosal microbiota in SIBO + compared with SIBO − IBS‐D patients, with increased MDI values but completely distinct genera increase or decrease between the duodenum and the rectum.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, no important differences were noted among Bacteroides-Prevotella group, Enterococcus, Escherichia coli, or Clostridium coccoides within these patients. In IBS-D patients, Lactobacillus and Bifidobacterium strains' concentration is lower compared with IBS-C, with the higher prevalence in Chinese subjects [43,44]. A study conducted by using cohorts from Iberian and Scandinavian Peninsula with different ages and diagnosed according to Rome II and III criteria concluded that dysbiosis was detected in 73% of IBS patients, as compared to healthy controls in which dysbiosis was 16% [45].…”
Section: It Is a Bug Situationmentioning
confidence: 99%
“…Irritable Bowel Syndrome (IBS) is one of the most common functional bowel disorders characterised by recurrent or chronic abdominal pain accompanied by changes in bowel habits or associated with bowel movements [1]. It affects 7% to 21% of the population worldwide and 1 to 16% in China [2]. It Short-chain fatty acids (SCFAs) are metabolites formed by gut microbiota from complex dietary carbohydrates.…”
Section: Introductionmentioning
confidence: 99%